2001
DOI: 10.1080/09638280010006151
|View full text |Cite
|
Sign up to set email alerts
|

Coming to terms with the shift in one's capabilities: a study of the adaptive process in persons with poliomyelitis sequelae

Abstract: Flexibility in choosing strategies facilitated participation in daily occupations. Requirements for this adaptive pattern were time, energy and ability to solve problems, accessible environments, access to information and support, and readiness to compensate with assistive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…The role of positive attitudes toward disability and optimism in adapting and replacing occupations resonates with the findings of Thorén-Jönsson (2001) and Duke, Leventhal, Brownlee, and Leventhal (2002).…”
Section: Downloaded By [University Of Kent] At 16:05 26 November 2014supporting
confidence: 78%
See 2 more Smart Citations
“…The role of positive attitudes toward disability and optimism in adapting and replacing occupations resonates with the findings of Thorén-Jönsson (2001) and Duke, Leventhal, Brownlee, and Leventhal (2002).…”
Section: Downloaded By [University Of Kent] At 16:05 26 November 2014supporting
confidence: 78%
“…Longitudinal studies have shown that people with rheumatoid arthritis who lose more social and leisure occupations report subsequent increases in depressive symptoms. This relationship is not entirely explained by decreased physical functioning (Katz & Yelin, 1995, 2001. Conversely, people who continue participating in valued leisure occupations despite their arthritis seem to enjoy better subjective well-being through gaining various benefits such as self-esteem, distraction from pain and other illness-related concerns, connection to the outside world, companionship, and social affirmation (Klinger, Spaulding, Polatajko, MacKinnon, & Miller, 1999;Parmelee, Harralson, Smith, & Schumacher, 2007;Zimmer, Hickey, & Searle, 1995).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Specifically, the inattentive phase [30], the stable phase of polio when there is no major physical loss, is similar to the pre-trauma state in the Health Change Process Theory. The next two phases, the phase of overloading and emotional crisis are represented in the Health Change Process Theory by trauma, which is experienced both prior to entering and during the Action Coping cycle.…”
Section: The Health Change Process Theory and Related Researchmentioning
confidence: 92%
“…For example, Thoren-Jonsson [30] investigated how people with post-polio syndrome achieved health when faced with significant, permanent and ongoing change and loss of physical and social function. Exploration of the coping strategies used resulted in the development of the 'conception of occupational self' construct that identified 'body image, sense of competence and values and goals' (p. 342) as the key components of healthy coping.…”
Section: The Health Change Process Theory and Related Researchmentioning
confidence: 99%